PENGARUH PENGEMBANGAN KARIR, IKLIM ORGANISASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI DINAS PENGELOLAAN SUMBER DAYA AIR KABUPATEN SIDENRENG RAPPANG - haeranah haeranah; maryadi maryadi; Irfan Setiawan; herni herni (Jurnal Ilmiah Wahana Bhakti Praja, 2024)
This research aims to examine the influence of career development, organizational climate and motivation on the performance of employees of the Sidenreng Rappang Regency Water Resources Management Service. This research uses quantitative methods. The research was carried out at the Sidenreng Rappang Regency Water Resources Management Service. The data used is primary data and secondary data obtained from the technique of distributing questionnaires to 52 respondents. The results of the research show that the career development variable has a negative effect on employee performance with a t-count <t-table value of (-0.174 < 2.009) and a sig.t value (0.862 > 0.05), the organizational climate variable has a positive and significant effect on employee performance variable with t-count > t-table (4.131 > 2.009) and sig.t value (0.000 < 0.05) on the third variable, namely motivation has a positive and significant effect on employee performance because t-count .>.table ( 3,443 < 2,009) and significant value (0.001 < 0.05). The simultaneous test has a positive and significant effect on employee performance, because the value of F-count > F-table (34,439 > 2.80) is significant, F is (0.000 < 0.05) while the determination test has a contribution to employee performance of 68.3% , while the rest is influenced by other variables not included in the research.